Pengaruh Modifikasi Alat Peraga Montessori Terhadap Kemampuan Motorik Kasar - Primayanti, Intan; Isyani, Isyani; Muliyani, Sri Erny (Universitas Hamzanwadi, 2022)
The Montessori method, which is a learning method that depends on each student, has the advantage of growing critical thinking, collaborating, and acting more assertively. Children with good cognition are characterized by problem-solving skills by prioritizing prosocial in every interaction, and vice versa. The lack of research in the field of sports related to motor and montessori movements, especially in West Nusa Tenggara and the results of observations at the MI Al Ijtihad school still use a monotonous learning pattern so that students tend to be passive, not independent and not confident so that it affects motor skills, in this study what is meant is rough motoric. The population in this study were students of MI Al-Ijtihad, totaling 20 students. In this study, researchers used purposive sampling with certain criteria. In this study, the researchers used instruments, namely the Zig-zag Running test and the Throwing the ball at the target. The type of research used is a quantitative experiment with a pre-test post-test group design. The data analysis technique used is the t-test through the t-test formula. From the results of statistical data analysis of the effect of modification of props on gross motor skills, the tcount X (throwing the ball at the target) of 5.446 simultaneously between Y and X1 draws conclusions from the table analysis at a significant level of 5% with the number of samples (n - 1), namely 19 is 2,869. So it can be concluded that ''There is an effect of modification of Montessori teaching aids on gross motor skills seen from tcount > ttable (5.446 > 2.869).